The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1969
DOI: 10.1002/recl.19690880602
|View full text |Cite
|
Sign up to set email alerts
|

The oxidation of dithiocarbamato complexes of nickel, copper and zinc

Abstract: Oxidation of N, N-di-n-butyldithiocarbamato (buzdtc) complexes of Cum, NiOI), ZnOI), Cd(I1) and Hg(II) is reported. Oxidation of Ni(bu2dtc)z with Clz, Brz, or of NiXz (X = CI, Br, Nos) with N,N,N',N'-tetra-n-butylthiuram disulfide (burtds) gives complexes of composition mi(buzdtc)3]X. These compounds are diamagnetic and dissolve in nitrobenzene as 1 : 1 electrolytes, their W spectra resemble that of the iso-electronic Co(buzdtc)s. The experimental data are in accord witli the assumption that in these compounds… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

1970
1970
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…The observed C-N distances are n o t conclusive with respect to the increase o f the C-N bond order as indicated by infrared and nm r measurements. T he difference in the C-S distances agree w ith the infrared spectra (Brinkhoff et al, 1970). …”
Section: Description Of the Moleculesupporting
confidence: 73%
See 1 more Smart Citation
“…The observed C-N distances are n o t conclusive with respect to the increase o f the C-N bond order as indicated by infrared and nm r measurements. T he difference in the C-S distances agree w ith the infrared spectra (Brinkhoff et al, 1970). …”
Section: Description Of the Moleculesupporting
confidence: 73%
“…In preceding papers, the preparations and properties o f diiodo-N ,N ,N ',N '-tetrabutylthiuram disulphidem ercury(II) (Brinkhoff et al, 1969) and o f the analogous ethyl derivative (Brinkhoff et al 1970) were reported. T he proposed m olecular structure was confirmed by an X -ray analysis o f the analogous methyl derivative, H gI2(M e4tds).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed addition of halogens results in ligand-centered oxidation to give tetrahedral thiuram disulfide complexes [ZnX 2 {R 2 CN(S)S-SC(S)NR 2 }] resulting from sulfur-sulfur bond formation (eqn. 16) [57]. The thiuram disulfide here is only weakly bound and can readily be displaced and thus could potentially be released in a biological system under oxidizing conditions.…”
Section: Current/amentioning
confidence: 96%
“…In this group of bis(dtc) complexes only the copper compounds showed a reversible behaviour. This is reflected in a remarkable way in the preparative oxidation of dtc complexes, only the copper complex giving a reaction product of the same stoichiometry C u (dtc)2+, nickel [10], palladium and platinum[ll] giving tris-complexes, M (dtc)3+, with the metal in the oxidation state +4.…”
Section: Voltammetric Studymentioning
confidence: 99%